Kepemilikan institusional, reputasi perusahaan, dan informasi akuntansi terhadap harga saham - Dirgantara Dahana Mokoginta (Universitas Kristen Maranatha, 2026)
This study aims to examine the effect of institutional ownership, corporate reputation proxied by firm age, and accounting information proxied by total assets, on stock prices. The study uses secondary data from financial statements and annual reports of companies listed in the LQ45 index during 2022-2024. The sample was selected using purposive sampling, and the data were analyzed using multiple linear regression with SPSS. The results show that institutional ownership and accounting information, proxied by total assets, do not affect stock prices, while corporate reputation, proxied by firm age, has a positive effect on stock prices. These findings indicate that, from agency relationship perspective, investors do not assess firms solely based on institutional ownership and the number of resources controlled by the company but also consider the firm’s track record of continuity as a reflection of management’s ability to maintain shareholders’ trust. This study implies that companies need to preserve their reputation consistently, as sustained business continuity can strengthen investor confidence and support stock price formation.